If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = 20x + 5 Reorder the terms: 1 = 5 + 20x Solving 1 = 5 + 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. 1 + -20x = 5 + 20x + -20x Combine like terms: 20x + -20x = 0 1 + -20x = 5 + 0 1 + -20x = 5 Add '-1' to each side of the equation. 1 + -1 + -20x = 5 + -1 Combine like terms: 1 + -1 = 0 0 + -20x = 5 + -1 -20x = 5 + -1 Combine like terms: 5 + -1 = 4 -20x = 4 Divide each side by '-20'. x = -0.2 Simplifying x = -0.2
| 14y-10y-14=67.56 | | 3b+2=5+b | | 1-3x+x=1-2x | | 4x^2-16x-15= | | 1.3x+4.7=-0.5 | | 3(4x-3)-8=4 | | 1+x=5x+25 | | 110=-10-7+x | | 14=t-21 | | -9x+6=-4-11x | | 6z^3+3-4z^3+5= | | 5a-3(a-8)=-40 | | x-(-44)=42 | | 3x+(5)=21 | | 16x^2+75x=28 | | 0.1h-0.02+0.4h=0.01 | | (6z)(6z)(6z)+3-((4z)(4z)(4z))+5= | | x+35=182 | | 1/3(x-3)=3x-2(x-1)+7/3 | | -5.2x=-0.468 | | a*x+b*x-1=8 | | -6k+2k+8k= | | 6z^3-4z^5= | | -5a+2a=-10+2a | | -3x^2-7x+2=6 | | -16x^2+75x+3=25 | | (4+4x)/3+(2-x)/2=19/6 | | (4x-20)+(2x+18)=180 | | 6b-5b+6b= | | 54=14-2p | | 3y+9=12x | | (1/2)x+2/3=1/6 |